Social systems according to specific systems theory - Pérez Durán, Gustavo de Jesús (Technium Social Sciences Journal, 2023)
The Specific Systems Theory (STS) proposes a system definition that describes them precisely based on six postulates that establish the sufficient and necessary elements for some real entity to be a system. This contradicts and rejects the traditional definition of Bertalanffy (1968), which mentions that a system is a conglomerate of interacting components. Based on the definition of system that is the main foundation of STS, the various types of social systems, which have been scarcely studied, are analyzed in this study. The literature that exists in this regard is abundant in arguments about their behavior, but all the arguments generated have been developed based on various concepts that have no relation to their systemic properties. In this work, social systems are analyzed from the perspective of their systemic characteristics, their systemic nature and their systemic properties. The definition of system that supports STS makes it possible to clearly and easily understand how social systems work and explain their behavior as systems and not simply as societies, which is the inadequate approach that has been used to discuss them until now.